Quantum dot energy relaxation mediated by plasmon emission in doped covalent semiconductor heterostructures - PEROVA, TANIA (American Physical Society, 2007)
The interaction between interface plasmons within a doped substrate and quantum dot electrons or holes has been theoretically studied in double heterostructures based on covalent semiconductors. The interface plasmon modes, the corresponding dispersion relationship, and the intraband carrier relaxation rate in quantum dots are reported. We find the critical points in the interface plasmon density of states for multilayered structures results in enhanced quantum dot intraband carrier relaxation when compared to that for a single heterostructure. A detailed discussion is made of the relaxation rate and the spectral position dependencies on the quantum dot layer thickness as well as on the dopant concentration. The material system considered was a p-Si?SiO2?air heterostructure with Ge quantum dots embedded in an SiO2 layer. This structure is typical of those used in technical applications.
PUBLISHED
Keywords: Mechanical and Manufacturing Engineering